(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The research has studied the repetition of the solar melasma ( The Solar Gaps ) and its impact on the climate of Baghdad city represented by the element of temperature over the period between ( 1980_ 2019 ) as a case study . The research has shed lights on the phenomenon to recognize its relationship with climate change which its effects has appeared clearly on the climate of the world The researcher depends on the analytical approach and the mass style to deal with the data and their way of representation in schedules and shapes . Following the way of studying the general direction. Hence, it is possible to recognize its circle of repetition for one year in order to notice the difference among the recognized repetitions to know the pattern of their occurrence and its relationship with the climate element ( the temperature). In addition, it adopts the data of the Iraqi Forcast and the Seismic Monitoring of temperature which has been recorded in Baghdad Station for the period of study . There was an attempt to find out the relationship between the phenomenon and the general temperature which is possible to know whether the relationship is statistically admitted or not.